Using E-Commerce to Attract Purchasing Power: A Study Case of Moslem Seller Communities - Ahmad Fadlan; Losi, Rizky Vita; Lubis, Rizal P. (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2023)
Abstract: The problems in this study are capital, working hours, length of business, and e-commerce are factors that affect the income of market traders. This study aimed to analyze the factors that affect the income of market traders in Pulo Brayan, Medan Barat District, after Covid-19. The data were processed using factor test analysis and then using multiple linear regression. The data obtained from distributing the questionnaires were processed using SPSS Software Version 22.0 For Windows. The results showed that the 4 variables analyzed using the factor analysis model consisted of 2 factors, namely the length of business and e-commerce factors. Based on multiple linear regression analysis, it showed that the length of business and e-commerce have a significant effect on the income of market traders in Pulo Brayan, Medan Barat District, after Covid-19. Keywords: E-Commerce; Moslem Seller Communities